Implementasi Supervisi Akademik Kepala Sekolah Melalui Pendekatan Kolaborasi Dalam Meningkatkan Kompetensi Guru Di SD Negeri 002 Lingga dan SD Negeri 003 Lingga - Ade Cipta Sari; Endang Sri Budi Herawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to describe the implementation of academic supervision by school principals through a collaborative approach in improving teacher competence at SD Negeri 002 Lingga and SD Negeri 003 Lingga. This research used a descriptive qualitative method. Data were collected through observation, structured interviews, and documentation involving the principals and teachers of both schools. The data were analyzed using the Miles and Huberman model, including data collection, data reduction, data display, and conclusion drawing. The validity of the data was strengthened through source and technique triangulation. The findings show that collaborative academic supervision has been implemented reasonably well and contributes to improving teacher competence, particularly in lesson planning, classroom management, and the use of varied learning strategies. The implementation is supported by open communication, principals' commitment, teachers' motivation, and a collaborative school culture. Nevertheless, several obstacles remain, including administrative workload, limited time, uneven digital literacy, resistance to feedback, and weak pre-supervision coordination. Therefore, more intensive planning, flexible supervision schedules, and stronger interpersonal communication skills among principals are required to optimize collaborative academic supervision.